Nurses' Work Environment and Practice as A Predictor of Burnout - Evangelia Meimeti; Athina Protopappa; Ioannis Moisoglou; Petros Galanis; Elissavet Lykoudi; Ioannis Tsolakoglou; Lampros Bizas; Aris Yfantis; Vasiliki Papanikolaou (ziauddin University, 2024)
Background: The proportion of nurses who experience burnout is particularly high. The study aimed to evaluate the demographics and working environment and practice of the nursing staff and their level of burnout. Methods: A cross-sectional study was implemented in three hospitals on n=290 nurses from July-August 2020. The Practice Environment Scale of the Nursing Work Index was used to evaluate nurses' work environment and assessment of participants' degree of burnout was carried out using the tool Copenhagen Burnout Inventory. Multiple linear regression was used to find association and p <0.05 was considered statistically significant. Results: The nurses' work environment was characterized as unhealthy, as the total score was 2.32, and four of the five subscales were also rated lower than 2.5. Nurses were found to experience moderate burnout. The subscale of personal burnout gathered the highest score. The nurses' practice in hospital affairs was associated with lower personal (b=−7.3,95%CI=-12.2 to -2.4, p=0.004), work-related (b=−9.5,95%CI=-14.4 to -4.8, p<0.001) and patient-related burnout (b=−10.6, 95%CI=-16.1 to -5.1, p<0.001). Also, nurse manager ability, leadership, and support of nurses were associated with lower personal (b=−6.5, 95% CI= -10.9 to -2, p=0.005) and work-related burnout (b = −5.8, 95%CI=-10.1 to -1.4, p=0.009). Conclusion: The nurses were found to experience significant burnout p < 0.001. But then again this was negatively influenced by their work environment. Keywords: Burnout, Hospital, Nurse, Work, Environment.